Tindak Pidana Pembunuhan oleh Seorang Ibu Terhadap Bayinya Setelah di Lahirkan - I Made Jaya Palguna; I Nyoman Gede Sugiarta; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
Violence against children is a form of human rights violation. Violence against children often occurs in the family environment where the family should receive protection, this has happened in the Gianyar district, Bali which was carried out by a biological mother against her newborn child, causing the child to die. The purpose of this research is to determine the legal regulation of the crime of murder by the mother of her baby after being born according to the law, as well as the criminal sanctions of the act of killing the mother of her baby after being born according to the law. The type of research in this research is normative research using primary legal materials and secondary legal materials. The technique of collecting legal materials is a literature research technique, namely by reviewing legal materials that intersect and then being categorized or classified and archived, written, quoted, summarized, and investigated as needed with a qualitative approach. Articles 341, 342, and 343 of the Criminal Code are also regulated in the Child Protection Law. With regard to criminal sanctions in such acts, based on Article 80 paragraphs 3 and 4 of Law no. 35 of 2014 concerning Child Protection, namely: perpetrators are sentenced to a maximum imprisonment of 15 years and/or a maximum fine of three billion rupiah.